Protection the Culture of Peace in International Law - Adham Abdulhadi, Haider (2022)
It is difficult to deny the importance of having a set of treaty legal rules that provide an appropriate legal framework for the protection of a culture of peace as long as we recognize that armed conflicts are international or non-international but are the product of intellectual convictions adopted by people in specific historical stages that contribute in one way or another to making the present and producing the future. Therefore, it is important to research in the areas of international protection for a culture of peace by first identifying aspects of the legal framework regulating the subject of the research, and then explaining the mechanisms of international protection, provided that the beginning begins with the definition of what is meant by a culture of peace, since defining the aforementioned concept will entail an important result related to determining the scope of the research Within the framework of the rules of general international law, and in light of goal (16) of the declared goals of the United Nations to achieve sustainable development where the focus is on encouraging the existence of human societies that believe in comprehensive peace for all as an effective tool to reach the concept of sustainable development as well as the possibility of resorting to A judiciary so that the realization of this aspect becomes available to all, and to establish, at all levels, effective institutions that are accountable, which requires envisioning a kind of complementarity between national frameworks that are supposed to cultivate faith in peace, coexistence, and respect for all human values despite the differences and diversity on the one hand and the frameworks.  The international community that seeks to promote reaching the same goals on the other hand, according to clear legal perceptions, wherever the first steps are confident and based on sound and realistic foundations applicable in practice, the goal of reaching the final goals will be more feasible than imagined